MENANGKAL ISLAM RADIKAL Upaya Santri Mlangi Yogyakarta dalam Mencegah Infiltrasi Paham Islam Radikal - Zainal Arifin (Istitut Ilmu Al-Qur'an (IIQ) An-Nur Yogyakarta Komplek PP An Nur Ngrukem PO BOX 135 Bantul 55702 Yogyakarta Tlp/Fax (0274) 6469012. http://jurnalannur.ac.id/, 2012)
The understanding of radical Islam is the root for movement of terrorism or religious radicalism. The movement articulation has the shape of violence or terror action, both in physical and non- physical forms of terror; threats, act of considering someone an infidel, polytheists accusation, act of blaming religious practices, and others. This study successfully makes radical Islam into category according to Mlangi santri based on thinking, behavior (action), and physical-symbolic. The strategy of Mlangi santri in preventing infiltration of radical Islam understanding is through a scientific approach (Aswaja ideological reinforcement), cultural tradition (religious traditions such as tahlilan, chant recounting Muhammad’life (zanji), abdul qadiran,) and builds structural-cultural network between santri, Muslim scholars, and government. Mlangi santris’ hope for government is government’s firmness in enforcing law against perpetrators of radical Islamic movements that do violence in action. For perpetrators of terrorism, government can sentence to death, brainwash, or cast into prison but isolate them.